2020
DOI: 10.1155/2020/6141728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Use of Staphylococcus carnosus in the Curing Process of Meat with a Reduced Amount of Sodium Nitrite on Colour, Residue Nitrite and Nitrate, Content of Nitrosyl Pigments, and Microbiological and the Sensory Quality of Cooked Meat Product

Abstract: The aim of the work was to apply the bacteria Staphylococcus carnosus ATCC 51365 in the meat curing process with the use of a reduced amount of sodium nitrite and to evaluate the effects of bacteria on residual nitrites and nitrates, the content of nitrosyl pigments, colour, pH, oxidation-reduction potential, microbiological, and the sensory quality of a cooked meat product. Three meat batters in cans were prepared: (C) a control batter cured with NaNO2—100 mg/kg, (L) a batter cured with NaNO2—15 mg/kg, and (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…In the further hours of light exposure, colour change of the model products was less intense (Tables 2 and 3). A similar dependence was reported in previous research [15].…”
Section: Colour Analysis After Production and Storagesupporting
confidence: 91%
See 3 more Smart Citations
“…In the further hours of light exposure, colour change of the model products was less intense (Tables 2 and 3). A similar dependence was reported in previous research [15].…”
Section: Colour Analysis After Production and Storagesupporting
confidence: 91%
“…Whereas Heaton et al [43] reported that decreasing the nitrite amount from 16 to 13 mg/kg had a significant effect on redness (a*) in cooked poultry rolls. In other research performed on finely ground cooked pork batters it was proved that when using 100 mg/kg of added sodium nitrite a significantly higher a* parameter value in the product was reported compared to a lower sodium nitrite amount (15 mg/kg) [15]. In other studies, sodium nitrite added in the production of Asian sausages (120 mg/kg), has been replaced with cochineal (0.05%), vitamin C (0.05%), vitamin E (0.05%), and celery (1%), which can be a natural source of nitrites and nitrates.…”
Section: Colour Analysis After Production and Storagementioning
confidence: 88%
See 2 more Smart Citations
“…The term "alternative curing" refers to the process that specific microorganisms reduce nitrate within these plant sources to nitrite. Nitrate-reducing bacteria which are used are coagulase negative cocci such as Staphylococcus (S.) carnosus or S. xylosus [25,38,[40][41][42]. The extent of nitrate reduction is achieved by certain temperature/time combinations [24,34,40]).…”
Section: Natural Curing-a Healthier Alternative?mentioning
confidence: 99%